2011
DOI: 10.4212/cjhp.v64i5.1069
|View full text |Cite
|
Sign up to set email alerts
|

Describing Intravenous Extravasation in Children (DIVE Study)

Abstract: Background: Extravasation, the inadvertent leakage of intravenous (IV) medication from the vein into the surrounding tissue, is a iatrogenic cause of patient injury. Extravasation has been reported to occur in 0.1% to 6.5% of hospital inpatients. The incidence may be higher among children because they have multiple risk factors, including small and fragile veins, decreased peripheral circulation, capillary leakage, and flexible subcutaneous tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 7 publications
3
55
0
2
Order By: Relevance
“…Infants and children have multiple risk factors for phlebitis and extravasation: small fragile veins, decreased peripheral circulation, capillary leakage, and flexible subcutaneous tissue. This makes short peripheral intravenous devices difficult to place and maintain, resulting in the need for repeated attempts at intravenous insertion, which can lead to complications, pain, and stress 14 , 25 , 26 …”
Section: Question 6: In Which Patients Is Peripheral Pn a Reasonable mentioning
confidence: 99%
“…Infants and children have multiple risk factors for phlebitis and extravasation: small fragile veins, decreased peripheral circulation, capillary leakage, and flexible subcutaneous tissue. This makes short peripheral intravenous devices difficult to place and maintain, resulting in the need for repeated attempts at intravenous insertion, which can lead to complications, pain, and stress 14 , 25 , 26 …”
Section: Question 6: In Which Patients Is Peripheral Pn a Reasonable mentioning
confidence: 99%
“…Although there is a reasonable availability of antidotes for extravasation injuries, only a minority of patients with these injuries receive an available antidote. 5 In a retrospective study of 42 documented pediatric extravasations, only 33% of patients received an appropriate antidote, although 81% of patients qualified for treatment. 5 Specific guidelines are available for radiographic contrast and chemotherapy extravasations, 1,6 but comprehensive evidence-based management recommendations for each specific extravasation are lacking.…”
mentioning
confidence: 99%
“…5 In a retrospective study of 42 documented pediatric extravasations, only 33% of patients received an appropriate antidote, although 81% of patients qualified for treatment. 5 Specific guidelines are available for radiographic contrast and chemotherapy extravasations, 1,6 but comprehensive evidence-based management recommendations for each specific extravasation are lacking. Thus, our main purpose was to evaluate the primary literature for available interventions for the management of extravasations and to provide recommendations based on treatment literature for specific therapeutic modalities for noncytotoxic medications.…”
mentioning
confidence: 99%
“…[12] Paquette and colleagues simply identify quantitatively one occurrence of vancomycin extravasation in patients under 18 years of age from one facility, without any further details. [13] Hoelen et al is the only case we found in the literature to describe tissue necrosis as a result of vancomycin extravasation, yet without a description of management of the event. [14] Thus, it is clear that information regarding skin necrosis as a result of vancomycin extravasation is scant, however, it is not unrecognized.…”
Section: Discussionmentioning
confidence: 98%